2010
DOI: 10.1007/s11205-010-9587-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of College Life (QCL) of Students: Further Validation of a Measure of Well-being

Abstract: This paper reports a study designed to further validate a measure of quality of college life (QCL) of university students (Sirgy, Grzeskowiak, Rahtz, Soc Indic Res 80(2), 343-360, 2007). Two studies were conducted: a replication study and an extension study. The replication study involved surveys of 10 different college campuses in different countries. The results of the replication study provided additional nomological (predictive) validation support of the measure based on a theoretical model mapping out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 22 publications
2
21
1
3
Order By: Relevance
“…One important finding from this study was that the QUL was predicted by applying being away strategies-during pre-departure and while at university-as well as other positive elements, which means that students who used those strategies found their university life better than students who did not. Consistent with other research (Sirgy et al 2010;Yu and Lee 2008), QCL / QUL has a crucial role in positive well-being. Unfortunately, our study did not include academic achievement, although in recent meta-analysis done by Bucker, Nuraydin, Simonsmeier, Schneider and Luhmann (2018), it was shown that low achievement does not necessarily result in negative well-being and high achievement does not automatically mean better quality of life.…”
Section: Predictors Of Student Well-beingsupporting
confidence: 91%
“…One important finding from this study was that the QUL was predicted by applying being away strategies-during pre-departure and while at university-as well as other positive elements, which means that students who used those strategies found their university life better than students who did not. Consistent with other research (Sirgy et al 2010;Yu and Lee 2008), QCL / QUL has a crucial role in positive well-being. Unfortunately, our study did not include academic achievement, although in recent meta-analysis done by Bucker, Nuraydin, Simonsmeier, Schneider and Luhmann (2018), it was shown that low achievement does not necessarily result in negative well-being and high achievement does not automatically mean better quality of life.…”
Section: Predictors Of Student Well-beingsupporting
confidence: 91%
“…), determinants of the growth, decline and competitiveness of organisations [61]; and (ii) as a set of non-economic factors, as a subject of research in the quality of academic life of students (QAL) (satisfaction with services, emotions felt in campus, etc. ), e.g., [62][63][64][65][66][67][68], or as a factor for assessing quality of work life (needs for satisfaction in a physical and emotional line) (QWL) [69][70][71][72][73].…”
Section: Sustainable Development Practices and Quality Of Lifementioning
confidence: 99%
“…Recent years have witnessed an exponential increase in the number of studies on QoL in educational environments in relation to the different individuals and groups therein [63,67,68,[77][78][79], more specifically in the areas of students' QAL, e.g., [64][65][66][67][68] and the QWL of teachers and researchers [70,71]. QAL can be assessed in terms of feelings of global satisfaction with the student's experience of life at university [80].…”
Section: Sustainable Development Practices and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the quality of academic life can be assessed in terms of feelings of global satisfaction with the student's life experience in his school environment. Students' satisfaction with academic management, social action, services and facilities has a significant influence on their quality of academic life [5], [6].…”
Section: Introductionmentioning
confidence: 99%